Dynamic capabilities and NGO sustainability: The mediating role of organizational ambidexterity in Lebanon - Shaya, Lara; Beydoun, Abdul Rahman; Abbas, Alaa (International Journal of Management and Sustainability, 2026)
Lebanon, a crisis-affected region, has witnessed an active presence of non-governmental organizations (NGOs) that play a crucial role in addressing developmental challenges. NGO’s strategic adaptability is required to sustain activities in a volatile environment. While dynamic capabilities sensing, seizing, and reconfiguring have been thoroughly investigated within corporations, they remain poorly understood in NGOs. This research studies the impact of dynamic capabilities on the sustainability performance of NGOs in Lebanon. It also investigates the role of organizational ambidexterity in mediating the relationship between dynamic capabilities and sustainability performance. The paper uses a quantitative approach, utilizing a structured survey questionnaire aimed at managers in NGOs. The analysis employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between dynamic capabilities, sustainability performance, and organizational ambidexterity. A total of 407 managers from diverse NGOs participated in the survey, providing data to evaluate the proposed hypotheses. The structural model demonstrated robust explanatory power, with R² values of 0.551 for sustainability performance. The findings reveal that reconfiguring (RC) and seizing (SEC) capabilities significantly influenced both OA and OS (p-value < 0.01). Notably, sensing capabilities (SC) impacted sustainability only through the mediating path of OA (beta = 0.067, p-value = 0.009). Organizational ambidexterity was found to be a powerful predictor of sustainability (beta = 0.434, p-value = 0.000) and serves as a vital mediator for all dynamic capabilities. These results suggest that NGOs in Lebanon achieve sustainability by leveraging dynamic capabilities to balance exploration and exploitation strategies, navigating environmental turbulence through strategic flexibility.